Formation of ethnocultural competence of future managers of socio-cultural activities: main areas of student training - Vereialova, Diana Vladimirovna (Этническая культура, 2025)
In this article the author analyzes the activities of teachers of the Chuvash State Institute of Culture and Arts in developing students’ ethnocultural competence. The research material is the results of the author’s observation of the process of professional training of managers of social and cultural activities. The observation was carried out according to such criteria as knowledge of material and spiritual-moral values of the ethnic community, traditions and rituals, nutrition, music, sports, ways of life support, geography of settlement; skills of correct behavior in situations of interethnic communication in accordance with the cultural characteristics of the interlocutor, including the choice of relevant means of verbal and non-verbal communication; personal qualities expressed in interest in certain cultural manifestations, the desire to join them. The development of the content of activities for the formation of students' ethnocultural competence is based on scientific and methodological research in the field of technology for training future leaders of amateur choreographic groups for stage interpretation of folk dance, technology for the formation and development of students' ethnic self-awareness, linguacultural and ethnopsychological features of the Chuvash mentality, technology for introducing students to folk art culture. To achieve positive results, it is necessary to integrate educational, research, cultural and educational activities, interaction with subjects of sociocultural activities, and innovative activities.